Psychic Income and Its Sources in Social Work - Idaitė, Monika; Daunytė, Agnė; Dunčytė, Ugnė; Gudienė, Goda; Jogielaitė, Evelina; Meištaitė, Greta; Vaitkevičiūtė, Lina; Venckutė, Gabrielė (Socialinė teorija, empirija, politika ir praktika, 2023)
Work is a mental and physical activity performed in order to receive a reward, which is usually understood as money. However, people work in a variety of jobs, and their job choices are not driven only by financial income. When working, we also receive psychic income – respect, gratitude, emotions, various experiences, and feelings. Psychic income is largely analyzed by economists and psychologists. In social work, as in medicine or pedagogy, psychic income is a significant part of the total income. The goal of the study is to identify sources of psychic income in social work. In order to determine the sources, a model of possible sources was constructed. The model is based on the ideas of Coleman, Bandura and Zukerman. The data for the test of the model was collected by surveying social workers. After the analysis, it can be stated that there are differences in psychic income between social workers depending on the sector they work in; statistically significant results were found in the case of social workers working in NGOs. The main sources of mental income are self-efficacy and the challenges and emotional experiences at work. Research also revealed that there are contradictions regarding the realization of power in social work as a source of psychic income, which requires additional research.